2016
DOI: 10.1016/j.jalz.2016.06.2358
|View full text |Cite
|
Sign up to set email alerts
|

Tract‐specific white matter hyperintensities disrupt neural network function in Alzheimer's disease

Abstract: Introduction White matter hyperintensities (WMHs) increase the risk of Alzheimer’s disease (AD). Whether WMHs are associated with the decline of functional neural networks in AD is debated. Method Resting-state functional magnetic resonance imaging and WMH were assessed in 78 subjects with increased amyloid levels on AV-45 positron emission tomography (PET) in different clinical stages of AD. We tested the association between WMH volume in major atlas-based fiber tract regions of interest (ROIs) and changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 57 publications
(77 reference statements)
7
53
1
Order By: Relevance
“…White matter hyperintensities (as defined by the standards for reporting vascular changes on neuroimaging (STRIVE) criteria) 43 were segmented based on FLAIR MRI scans, using a semiautomated method that was described previously 44 . (For a more detailed description see supplementary methods.)…”
Section: Methodsmentioning
confidence: 99%
“…White matter hyperintensities (as defined by the standards for reporting vascular changes on neuroimaging (STRIVE) criteria) 43 were segmented based on FLAIR MRI scans, using a semiautomated method that was described previously 44 . (For a more detailed description see supplementary methods.)…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is possible that vascular and amyloid deposition are synergistically involved in Alzheimer’s disease and contribute to white matter alterations. Higher levels of white matter alterations are associated with FDG-PET decline ( Lo et al , 2012 ; Glodzik et al , 2014 ; Marnane et al , 2016 ), higher grey matter atrophy ( Bos et al , 2017 ), reduced functional network integrity ( Taylor et al , 2017 ) and worse cognitive decline ( Lo et al , 2012 ; Marchant et al , 2012 ; Vemuri et al , 2015 ). Thus, white matter alterations, possibly stemming from cerebrovascular disease, may add to the effects of amyloid deposition on neurodegeneration and cognition in ageing and Alzheimer’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the white matter microstructure in preclinical phases of AD has revealed that the cognitively normal elderly with positive Aβ-42 show increased DA in the left IFOF compared to the aged with negative Aβ-42 [37]. Moreover, the macroscopic research of white matter injury in AD also provided the evidence that the volume of white matter hyperintensity within IFOF was the highest among all ber tracts and correlated with decreased functional connectivity in IFOFconnected areas of default mode network [38]. Therefore, the above ndings indicated that left-sided white matter microstructural integrity in the ber tract level may be more vulnerable and the left IFOF may be a potential biomarker for the early identi cation of AD.…”
Section: Discussionmentioning
confidence: 99%